Discrete Mathematics with Graph Theory (3rd Edition) 131

Discrete Mathematics with Graph Theory (3rd Edition) 131 -...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Section 5.2 Exercises 5.2 1. (a) [BB] a1 = 1; ak+1 = 5ak for k 2': 1. (b) = 5; = ak - 2 for k 2': (c) = 4; a2 = 1; ak+2 = - for k 2': (d) There are two possibilities: = 1; = + (_1)k+1k for k Also, = 1, = 2, = ak-2 + (_1)k for k 3. 2. (a) [BB] 16,8,4,2,1,1,1; (c) 18,9,4,2,1,1,1; (b) 17,8,4,2,1,1,1; (d) 100,50,25,12,6,3,1. 129 3. When n = 3 n - 1 = 30 = 1, which agrees with a1. Now assume the result is true for n = k; that is, assume = 3 k - 1 . We must prove the result for n = k + that is, we must prove that = 3(k+1)-1 = 3 k . Now = 3ak = 3(3 k - 1 ) (by the induction hypothesis) = 3 k , as required. By the Principle of Mathematical Induction, the result is true for all n 4. [BB] When n = 1, the formula becomes (1-1)(1+ 2 1(1 2 +1+ 2 ) = 0, which is Now assume that the formula is correct when n = k. When n = k + 1, (k 1) 3 (k 1)3 (k - 1)(k + 2)(k 2 + k + 2) = + + = + + 4 4k 3 + 12k2 + 12k + 4 + k4 + 2k 3 + k 2 - 4 4 + 6k 3 + 13k 2 + 12k 4 k(k + 3)(k 2 + 3k + 4) = --'------'--'------'-
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 11/08/2010 for the course MATH discrete m taught by Professor Any during the Summer '10 term at FSU.

Ask a homework question - tutors are online